2020
DOI: 10.1002/ehf2.13042
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of exogenous atrial natriuretic peptide in patients with heart failure with preserved ejection fraction: deficiency of atrial natriuretic peptide and replacement therapy

Abstract: Aims Exogenous atrial natriuretic peptide (ANP) may be a logical treatment for heart failure (HF) patients with ANP deficiency. Lower ANP concentrations may result from HF with preserved ejection fraction (HFpEF), which also results in lower brain natriuretic peptide levels in HFpEF relative to HF with reduced ejection fraction (HFrEF), although clinical features regarding circulating ANP in HFpEF and HFrEF have not been fully investigated during acute HF. Here, we characterized the differential regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…Few previous studies have demonstrated the pure diuretic efficacy of exogenous ANP (or BNP) in AHF. Consistent with our recent report, 9 baseline plasma ANP levels independently predicted the diuretic response to exogenous ANP. This finding supports the recent emerging paradigm that ANP deficiency is a useful therapeutic target for ANP replacement therapy in HF, 19–21 similar to hormonal deficiency in other organs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Few previous studies have demonstrated the pure diuretic efficacy of exogenous ANP (or BNP) in AHF. Consistent with our recent report, 9 baseline plasma ANP levels independently predicted the diuretic response to exogenous ANP. This finding supports the recent emerging paradigm that ANP deficiency is a useful therapeutic target for ANP replacement therapy in HF, 19–21 similar to hormonal deficiency in other organs.…”
Section: Discussionsupporting
confidence: 92%
“…Among the differences in patient characteristics according to baseline ANP and arginine vasopressin status, it was noteworthy that lower ANP levels were significantly associated with higher LVEF and higher rate of HFpEF, although arginine vasopressin concentrations were not associated with LVEF status. LVEF is significantly associated with the diuretic effect of exogenous ANP in AHF, 9 whereas arginine vasopressin status was not associated with LVEF in this study. Meanwhile, higher plasma arginine vasopressin levels were linked to higher plasma osmolality and were also associated with a trend towards higher urinary osmolality.…”
Section: Discussioncontrasting
confidence: 68%
“…Insulin resistance due to lower plasma BNP levels could also contribute to the development of diastolic dysfunction because insulin resistance is considered one of the causes of its development 11 . In a study of acute HF, preserved ejection fraction (EF) and lower baseline ANP levels were reported to be independent predictors of a greater diuretic effect of exogenous ANP, and it has been suggested that patients with HF and preserved EF might have NP deficiency and hence represent a promising therapeutic target for modulating circulating NP levels 39 . Additionally, LCZ696 (sacubitril valsartan sodium hydrate), which enhances the action of NPs by inhibiting neprilysin, increases insulin sensitivity index among patients with obesity and hypertension 40 .…”
Section: Discussionmentioning
confidence: 99%
“… 11 In a study of acute HF, preserved ejection fraction (EF) and lower baseline ANP levels were reported to be independent predictors of a greater diuretic effect of exogenous ANP, and it has been suggested that patients with HF and preserved EF might have NP deficiency and hence represent a promising therapeutic target for modulating circulating NP levels. 39 Additionally, LCZ696 (sacubitril valsartan sodium hydrate), which enhances the action of NPs by inhibiting neprilysin, increases insulin sensitivity index among patients with obesity and hypertension. 40 Therefore, neprilysin inhibition might be efficacious in individuals with lower basal BNP levels for preventing the development of LV concentric remodelling beyond the effects of antihypertensive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the association between heart rate reduction and prognosis in patients with AHF presenting with AF has been the focus of several recent studies [ 3 , 4 ]. Furthermore, the presence of AF is also a good predictor of the greater diuretic effect of exogenous atrial natriuretic peptide in patients with AHF [5] . As heart failure is a major additional risk factor for ischemic stroke in patients with AF, the establishment of appropriate and effective anticoagulant therapy is a major clinical challenge [6] .…”
Section: Introductionmentioning
confidence: 99%